Community medicine: perceptions among medical students and career preference: a cross sectional study - Sadawarte, Mandar K.; Kakeri, Meena K.; Nandanwar, Deepika Y. (International Journal Of Community Medicine And Public Health, 2017)
Background: Learning community medicine helps the student not only to become a good clinician but also a good manager, educator and a researcher. Community medicine exposes medical students to primary and secondary healthcare settings and to promotive, preventive, curative and rehabilitative health services. This helps them to serve the needy people with a holistic approach. The objective is to find the perceptions of medical students regarding Community Medicine as a Medical Subject and as a career preference. Methods: A cross-sectional study was conducted over a period of 2 months. It was conducted on 200 students of Final year part I of MBBS in a tertiary care hospital by using universal sampling method. Data was collected from all the students using a self-administered pre-tested questionnaire using Likert’s scale. Results: Total 212 students participated in this study out of which 125 were boys and 87 were girls. The perceptions of students about community medicine were that this field gives an overall view of community’s medical needs. Curriculum is too vast and needs to be modified. More research should be done in community. Teaching methodology should be modified for making topics interesting. More number of girls was interested in taking community medicine as a career. Conclusions: Students perceptions regarding the field of community medicine showed that community medicine is essential for successful medical practice. But the teachers must make this subject more interesting by giving more practical insight and improving the teaching modalities.